Eksistensi Bisnis Melalui Penerapan Strategi Permodalan, Literasi Keuangan dan Legalitas Usaha Bagi Warga di Kota Surabaya - Dimas Prayudha Anggoro; Muhammad Afif Alhalim; Gyska Indah Harya; Isna Diva Nur Priardhina; Adyatma Nagata (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
The objective of this community service activity is to enhance the knowledge of residents in Menur Pumpungan Village, Surabaya, regarding business financing, financial management, and business legality. Micro, Small, and Medium Enterprises (MSMES) play a crucial role in the national economy. However, challenges faced by MSMEs, such as limited capital, low financial literacy, and legal issues, often hinder business growth and sustainability. Many MSMES do not yet have a Business Identification Number (NIB) for their operations, and some are even unaware of what an NIB is and its benefits. The methods used include socialization, training, and mentoring. The results of this activity show that 81% of residents understand how to improve the management and legality of their businesses to enhance their market value. The community in Menur Pumpungan Village is able to conduct field surveys to assess conditions and gather data and information related to business issues after consulting with the socialization team. The socialization and mentoring team provided appropriate solutions to partners. However, during the evaluation, 19% of residents/business owners still do not understand the KUR program, and some believe that access to KUR is difficult due to its complex procedures.